Compound‐Specific Isotope Analyses to Assess TCE Biodegradation in a Fractured Dolomitic Aquifer. Issue 1 (5th July 2016) - Clark, Justin A.; Stotler, Randy L.; Frape, Shaun K.; Illman, Walter A.
Abstract: The potential for trichloroethene (TCE) biodegradation in a fractured dolomite aquifer at a former chemical disposal site in Smithville, Ontario, Canada, is assessed using chemical analysis and TCE and cis‐ DCE compound‐specific isotope analysis of carbon and chlorine collected over a 16‐month period. Groundwater redox conditions change from suboxic to much more reducing environments within and around the plume, indicating that oxidation of organic contaminants and degradation products is occurring at the study site. TCE and cis ‐DCE were observed in 13 of 14 wells sampled. VC, ethene, and/or ethane were also observed in ten wells, indicating that partial/full dechlorination has occurred. Chlorine isotopic values (δ 37 Cl) range between 1.39 to 4.69‰ SMOC for TCE, and 3.57 to 13.86‰ SMOC for cis ‐DCE. Carbon isotopic values range between −28.9 and −20.7‰ VPDB for TCE, and −26.5 and −11.8‰ VPDB for cis ‐DCE. In most wells, isotopic values remained steady over the 15‐month study. Isotopic enrichment from TCE to cis ‐DCE varied between 0 and 13‰ for carbon and 1 and 4‰ for chlorine. Calculated chlorine‐carbon isotopic enrichment ratios (ϵCl /ϵC ) were 0.18 for TCE and 0.69 for cis ‐DCE. Combined, isotopic and chemical data indicate very little dechlorination is occurring near the source zone, but suggest bacterially mediated degradation is occurring closer to the edges of the plume. Abstract : Article impact statement : Compound‐specific carbon and chlorine stable isotopes indicate natural attenuation of TCE to cis ‐DCE in a historic fractured rock spill.